2016
DOI: 10.1002/2016wr018866
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm effect on soil hydraulic properties: Experimental investigation using soil‐grown real biofilm

Abstract: Understanding the influence of attached microbial biomass on water flow in variably saturated soils is crucial for many engineered flow systems. So far, the investigation of the effects of microbial biomass has been mainly limited to water‐saturated systems. We have assessed the influence of biofilms on the soil hydraulic properties under variably saturated conditions. A sandy soil was incubated with Pseudomonas Putida and the hydraulic properties of the incubated soil were determined by a combination of metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 83 publications
4
55
1
Order By: Relevance
“…Kroener et al (2018) showed that chia seed mucilage decreased the soil saturated hydraulic conductivity of soils of varying texture, but less is known about its impact on the unsaturated hydraulic conductivity. We expect that the relative unsaturated hydraulic conductivity (ratio between conductivity and saturated conductivity) drops more gradually when mucilage is present, as shown for soils embedded with EPS (Volk et al, 2016), because of the maintained continuity of the liquid phase. But the question, whether mucilage does increase the hydraulic conductivity and diffusion coefficient in dry soils, remains open.…”
Section: Retention and Transport Properties Of The Rhizospherementioning
confidence: 85%
See 1 more Smart Citation
“…Kroener et al (2018) showed that chia seed mucilage decreased the soil saturated hydraulic conductivity of soils of varying texture, but less is known about its impact on the unsaturated hydraulic conductivity. We expect that the relative unsaturated hydraulic conductivity (ratio between conductivity and saturated conductivity) drops more gradually when mucilage is present, as shown for soils embedded with EPS (Volk et al, 2016), because of the maintained continuity of the liquid phase. But the question, whether mucilage does increase the hydraulic conductivity and diffusion coefficient in dry soils, remains open.…”
Section: Retention and Transport Properties Of The Rhizospherementioning
confidence: 85%
“…In a provoking paper entitled “The Physics of Soil Water Physics”, Sposito () challenged soil physicists claiming that the fundamental physics of water flow in soils had already been explained by Buckingham () and Richards (), and since then the achievements in soil physics mainly consisted in technical improvements, either experimental or numerical. Sposito's paper is a plea for researching the fundamental physics of water in soils.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high viscosity, mucilage and EPS decrease the saturated soil hydraulic conductivity (Kroener et al, 2014; Volk et al, 2016). The effects on unsaturated conditions are less clear.…”
Section: Physical Properties Of Extracellular Polymeric Substances (Ementioning
confidence: 99%
“…The effects on unsaturated conditions are less clear. The decline in hydraulic conductivity with soil water potential was less steep in soils inoculated with biofilm forming bacteria ( Pseudomonas putida ) (Volk et al, 2016). In fine‐textured soils, EPS was even shown to increase the unsaturated conductivity (Volk et al, 2016).…”
Section: Physical Properties Of Extracellular Polymeric Substances (Ementioning
confidence: 99%
See 1 more Smart Citation